Dialéctica de la ilustración en clave de max horkheimer y theodor adorno: entrelazamiento de la barbarie y la racionalidad (2018)
In this article the fundaments of the philosophy of Adorno and Horkheimer are analyzed based on the dialectic of history that is exposed in the work Dialectic of the Enlightenment. For both authors, the causes of the regression of the Enlightenment, evident in social institutions and concrete historical forms, conﬁrm the thesis that such causes are found in it. For this reason, they refer to myth, as the ﬁrst expression of logical rationality, to demonstrate that the degenerative principle, present in the Enlightenment, also exists in it. In this way, initially the ﬁrst part of the thesis will be analyzed, the myth is already Illustration. Later the second part of the thesis: Enlightenment becomes mythology. Both theses allow the authors to verify that since prehistory, rationality is intertwined with barbarism. However, for the frankfurtians it is not simply a matter of denying and eliminating the rationality, but of tracking the possibilities of their salvation.